DNA Ligase Mutants of Escherichia coli - Gellert, Martin (1970)
A procedure is described for the isolation of Escherichia coli mutants with either excess or deficient DNA ligase activity. A mutant that overproduces DNA ligase supports the growth of ligase-defective (gene 30 mutant) T4 phages. Even T4 rII-gene 30 double mutants, which are able to grow in normal E. coli, cannot grow in cells deficient in DNA ligase. A functional DNA ligase, supplied either by the phage or the host, thus seems to be required for T4 growth. An E. coli strain that makes a temperature-sensitive DNA ligase becomes radiation-sensitive at high temperature, but otherwise grows normally and shows no obvious defect in DNA replication.